Comparative analysis of the morphology, ultrastructure and glycosylation pattern of the jejunum and ileum of the wild rodent Lagostomus maximus - Tano de la Hoz, María Florencia (2016)
Morphological and histochemical analyses were performed to characterize the histology, ultrastructure, and glycosylation pattern of the jejunum and ileum of the wild rodent Lagostomus maximus. Enterocytes, goblet cells, Paneth cells, and enteroendocrine cells were identified in both intestinal epithelia. Two morphological types of enterocytes wereidentified only in the ileum based on their cytoplasm electron density. Although the histological and ultrastructural examination showed that the epithelia of both anatomical regions were morphologically similar, a certain specialization in their secretory products was evident. The glycosylation pattern of the jejunum and ileum was characterized in situ by histochemical and lectin histochemical methods. Histochemical results revealed the presence of carboxylated and sulfated gycoconjugates in both regions, although sulfomucins were clearly prevalent in the ileum. Sialic acid was highly O-acetylated and particularly abundant in the jejunum. The KOH/PA*/Bh/PAS technique evidenced a more intense histochemical reaction in the jejunal than in the ileum goblet cells, demonstrating a reduction of neutral mucin secretion in the distal small intestine. Further specific differences were revealed by lectin histochemistry. These data evidenced that the nature of mucus varies at different anatomical regions, probably adapted to physiological requirements.